Experimental assessment of the fluid bulk temperature profile in a mini channel through inversion of external surface temperature measurements. (April 2015) - Rouizi, Y.; Al Hadad, W.; Maillet, D.; Jannot, Y.
Abstract: In previous works, a semi-analytical model allowing the simulation of heat transfer in a mini-channel has been presented. This model does not rely on the local internal heat transfer coefficient distribution. The focus of this study concerns the experimental characterization of the conjugate heat transfer in a vertical flat mini-channel of 1 mm thickness. The objective here is to validate experimentally the previous approach on an experimental bench by using infrared thermography measurements on the external faces of the channel. The temperature observations are used then within an inverse approach in order to recover the external heat transfer coefficient (air) over the external faces (parameter estimation problem) as well as the internal boundary conditions (function estimation inverse problem). The interest of such an inverse approach, coupling a model and measurements, is to avoid introducing an intrusive instrumentation at this scale. It allows to validate a semi-analytical heat transfer model that takes into account conduction and advection in the fluid as well as conduction in the solid (conjugate heat transfer) without the use of any internal heat transfer coefficient.